PRAGMATIC ASPECTS OF THE USE OF NONVERBAL MEANS IN ZULFIYA ISRAILOVA’S POEMS (SCIENCE TIME JOURNAL, 2026)
This article examines the pragmatic aspects of the use of nonverbal means in the poetry of Zulfiya Isroilova. The main objective of the study is to identify nonverbal elements occurring in the poet’s poems and to determine their communicative and emotional functions. The paper provides a detailed analysis of the use of facial expressions, pauses, intonation, and other nonverbal means within poetic context, as well as their pragmatic meanings and sociolinguistic functions. The results of the research contribute to revealing the communicative effectiveness of nonverbal means in Zulfiya’s poetry.